The Influence of Authentic Leadership and Work Environment on Teachers Performance - Hada Hayata; Sugiarto sugiarto; Siti Rochanah (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research was conducted to find that authentic leadership and work environment influence partially and simultaneously on the performance of teacher at  Junior High School in Bekasi. This study using a  descriptive quantitative approach regression models. The population in this study was 306 teachers, and the sample was taken using the Slovin formula with an error rate of 5% so that there were 75 teachers. The instrument used was a questionnaire distributed via Google Form based on the Likert scale. At the same time, hypothesis testing is obtained based on the results of the t-test, F test and the coefficient of determination test. The results prove that there are several conclusions, namely: (1) authentic leadership has a positive effect on the performance of Junior High School teachers; (2) The work environment has a positive and significant effect on the performance of Junior High School teachers; (3) Authentic leadership and work environment simultaneously influence the performance of Junior High School teachers with the results of the test value of the coefficient of determination of 0.673 or 67.3%, meaning that authentic leadership and work environment have an influence on performance by 67.3% and the rest 32.7% is influenced by variables not studied.